The African-Jamaican Aesthetic Cultural Retention and Transformation Across Borders (Volume 196) - Tomlinson, Lisa (Brill, 2017)
The African-Jamaican Aesthetic explores the ways in which diasporic African-Jamaican writers employ cultural referents aesthetically in their literary works to challenge dominant European literary discourses; articulate concerns about racialization and belonging; and preserve and enact cultural continuities in their new environment(s). The creative works considered provide insight into how local and indigenous Caribbean knowledges are both changed by the transfer to new, diasporic locales and reflect a unified consciousness of African-Jamaican roots and culture. The works surveyed also reveal significant connections with a 'past' Africa. Indeed, Africa is treated as a central source of aesthetic influence in these writers' expression of local cultures and indigenous knowledges. Aspects covered include language (Jamaican Patwa), religion, folklore, music, and dance to identify the continuities in an African-Jamaican aesthetic, which is understood here as an ongoing dialogue of cultural memory between the Caribbean, Africa, and diasporic spaces. Writers discussed include Claude McKay, Una Marson, Louise Bennett, Afua Cooper, Lillian Allen, Linton Kwesi Johnson, Benjamin Zephaniah, Lillian Allen, Jean 'Binta' Breeze, Makeda Silvera, and Joan Riley